An exploration of psychological and socio-cultural facets in perinatal distress of Pakistani couples: a triangulated qualitative study - Sameera Shafiq (BMC, 2024)
Abstract The phenomenon of perinatal distress in terms of depression, anxiety, bipolar, and psychotic disorders is well-explored in the West but barely investigated in South Asia; particularly research evidence highlighting the cultural expression of couples' mental health with respect to Pakistan is rare. The purpose of this research is to focus on the exploration of psycho-socio-cultural expression of couples' perinatal distress and coping strategies used in the Pakistani context in relation to maternal and paternal mental health, with implications for the wellbeing of their unborn or born progeny. The research design focused on qualitative interpretative approaches. In data triangulation, reflexive thematic analysis and interpretative phenomenological analyses were applied on the verbatim of the semi-structured interviews conducted with the mental health professionals (n = 9) and the couples (n = 8), screened positive for perinatal distress. Four couples were screened out of 325 perinatal women visiting the gynaecological ward of Aziz Bhatti Shaheed Teaching Hospital, Gujrat. Edinburg Postnatal Depression Scale, Generalized Anxiety Disorder-7 and Washington Early Recognition Center Affectivity and Psychosis Screen are the standardized instruments considered to be used for screening perinatal distress among couples. The Urdu version of WERCAP Screen was developed by a standardized forward-backward translation procedure. The rest of the four couples were purposively selected from the psychiatric ward of the same hospital. The Simplified Negative and Positive Symptoms Interviews were administered to the couples after getting approval for the Urdu version form. All couples were probed with an indigenously developed Structured Clinical Interview Schedule for DSM Disorders based on DSM-5-TR. The triangulation carried out with reflexive thematic analysis and interpretative phenomenological analysis revealed cultural conception of perinatal distress as perceived by the mental health professionals and experienced by the couples during the antenatal and postnatal period of their lives. They were enlightened with a constructive view aimed at promoting transformational change in terms of their mental health care and coping. The implications suggested implementation of a psychotherapeutic intervention for reduction in the level of distress and subsequent enhancement of well-being in couples during the perinatal period.